Proses Pembuatan Jig Magazine Pada Mesin CNC Turning dan Milling Di PT XYZ - Habibie Mochammad; Kardiman Kardiman (Jurnal Ilmiah Wahana Pendidikan, 2022)
Developments in manufacturing technology companies are currently growing rapidly, especially industries with large-scale production in a very short time. By using a computer, it can create a system where the production process can be carried out quickly and with quality. This technology is embedded in machine tools that are usually used for mass production, namely CNC (Computer Numeric Control). In addition, using a CNC machine is more efficient than conventional machines because it can save time, be more accurate, flexible and efficient. Therefore, many companies are using this CNC machine in the modern era [3]. One of the companies engaged in this machining is PT. XYZ, where one of its products is produced using a CNC machine, namely the manufacture of a jig magazine. After analyzing the jig magazine manufacture on the CNC – 450 machine, the Jig and Fixture Design that was made can be used as a tool. As well as in the production of making Jig Magazine products, Jig and Fixture designs can provide a decrease in total time, product manufacture, product quality improvement, productivity improvement and cost savings, Feeding speed in the initial process is 1000 mm/min, The slope of the Support bar guide is 3, 18o, The obtained gripping force is 2304.03N